Impaired probabilistic reversal learning in youths with mood and anxiety disorders - Dickstein, D. P.; Finger, E. C.; Brotman, M. A.; Rich, B. A.; Pine, D. S.; Blair, J. R.; Leibenluft, E. (Psychological medicine, 2010)
From an affective neuroscience perspective, our understanding of psychiatric illness may be advanced by neuropsychological test paradigms probing emotional processes. Reversal learning is one such process, whereby subjects must first acquire stimulus/reward and stimulus/punishment associations through trial and error and then reverse them. We sought to determine the specificity of previously demonstrated reversal learning impairments in youths with bipolar disorder (BD) by now comparing BD youths to those with severe mood dysregulation (SMD), major depressive disorder (MDD), anxiety (ANX), and healthy controls. We administered the probabilistic response reversal (PRR) task to 165 pediatric participants aged 7-17 years with BD (n=35), SMD (n=35), ANX (n=42), MDD (n=18) and normal controls (NC; n=35). Our primary analysis compared PRR performance across all five groups matched for age, sex and IQ. Compared to typically developing controls, probabilistic reversal learning was impaired in BD youths, with a trend in those with MDD (p=0.07). Our results suggest that reversal learning deficits are present in youths with BD and possibly those with MDD. Further work is necessary to elucidate the specificity of neural mechanisms underlying such behavioral deficits.